TRPV1 Antagonism by Capsazepine Modulates Innate Immune Response in Mice Infected with Plasmodium berghei ANKA - Elizabeth S. Fernandes; Carolina X. L. Brito; Simone A. Teixeira; Renato Barboza; Aramys S. dos Reis; Ana Paula S. Azevedo-Santos; Marcelo Muscará; Soraia K. P. Costa; Claudio R. F. Marinho; Susan D. Brain; Marcos A. G. Grisotto (Mediators of Inflammation)
Thousands of people suffer from severe malaria every year. The innate immune response plays a determinant role in host’s defence to malaria. Transient receptor potential vanilloid 1 (TRPV1) modulates macrophage-mediated responses in sepsis, but its role in other pathogenic diseases has never been addressed. We investigated the effects of capsazepine, a TRPV1 antagonist, in malaria. C57BL/6 mice received 105 red blood cells infected with Plasmodium berghei ANKA intraperitoneally. Noninfected mice were used as controls. Capsazepine or vehicle was given intraperitoneally for 6 days. Mice were culled on day 7 after infection and blood and spleen cell phenotype and activation were evaluated. Capsazepine decreased circulating but not spleen F4/80+Ly6G+ cell numbers as well as activation of both F4/80+and F4/80+Ly6G+ cells in infected animals. In addition, capsazepine increased circulating but not spleen GR1+ and natural killer (NK) population, without interfering with natural killer T (NKT) cell numbers and blood NK and NKT activation. However, capsazepine diminished CD69 expression in spleen NKT but not NK cells. Infection increased lipid peroxidation and the release of TNFα and IFNγ, although capsazepine-treated group exhibited lower levels of lipid peroxidation and TNFα. Capsazepine treatment did not affect parasitaemia. Overall, TRPV1 antagonism modulates the innate immune response to malaria.